1969
DOI: 10.1139/g69-083
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding and Heterosis in Autotetraploid Alfalfa. I. Fertility

Abstract: Certain aspects in the quantitative genetics of autotetraploid populations have been developed into a deterministic model. The use of two mating systems, inbreeding and hybridization, on the fertility of two alfalfa clones gave results which were in close agreement with the proposed model. The interactions between more than two alleles, whether identical or not, were important in the expression of heterosis. Performance of hybrids became weaker and weaker as the parents were more and more inbred. It was possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1970
1970
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Wilsie (1958) showed that one generation of selfing resulted in a mean loss of 20 to 30% in vegetative vigor and 80 to 90% in self‐fertility. Dessureaux and Gallais (1969) investigated the pattern of inbreeding depression in two specific alfalfa genotypes and the impact on the first‐generation hybrid as the parents became more inbred. Inbreeding depression increased in each generation, and by the third generation, the progeny had practically become self‐sterile.…”
Section: Resultsmentioning
confidence: 99%
“…Wilsie (1958) showed that one generation of selfing resulted in a mean loss of 20 to 30% in vegetative vigor and 80 to 90% in self‐fertility. Dessureaux and Gallais (1969) investigated the pattern of inbreeding depression in two specific alfalfa genotypes and the impact on the first‐generation hybrid as the parents became more inbred. Inbreeding depression increased in each generation, and by the third generation, the progeny had practically become self‐sterile.…”
Section: Resultsmentioning
confidence: 99%
“…performance of the F1 (3,4). Thus it is more difficult to capitalize on advantages of hybrid vigor in seed reproduced po1ysomics than it is in seed reproduced diploids, disomic po1yp1oids, or in asexually reproduced crops.…”
mentioning
confidence: 99%
“…Depending on the original heterozygosity at a locus, inbreeding or the loss of heterozygosity will be affected differently. If a locus is duplex or simplex, the loss of allelic interactions at that locus will closely follow the inbreeding coefficient expectation and result in a linear response (Dessureaux & Gallais, 1969). However, if trigenic and tetragenic loci are involved, the loss of the three and four allele interactions will be more rapid than the F value predicts, resulting in a nonlinear response to inbreeding (Busbice & Wilsie, 1966).…”
Section: Parental Combining Ability and Inbreeding Depressionmentioning
confidence: 99%